Intestinal Stem Cell-on-Chip to Study Human Host-Microbiota Interaction - Siwczak, Fatina; Loffet, Elise; Kaminska, Mathilda; Koceva, Hristina; Mahe, Maxime M.; Mosig, Alexander S. (Frontiers in Immunology, 2021)
The gut is a tubular organ responsible for digestion and harbors our intestinal microbiome. This organ is composed of a multitude of specialized cell types arranged in complex barrier-forming crypts and villi covered by a mucosal layer controlling nutrient passage and protecting from invading pathogens. The development and self-renewal of the intestinal epithelium is guided by niche signals controlling the differentiation of specific cell types along the crypt-villus axis in the epithelium. The emergence of mIcrophysiological systems, or organ-on-chips, has paved the way to study the intestinal epithelium within a dynamic and controlled environment. In this review, we describe the use of organ-on-chip technology to control and guide these differentiation processes in vitro. We further discuss current applications and forthcoming strategies to investigate the mechanistic processes of intestinal stem cell differentiation, tissue formation, and the interaction of the intestine with the microbiota in the context of gastrointestinal diseases.